Biomechanical effects of periodontal status on molar sequential distalization with clear aligners: a finite element study - Yanning Ma; Xinyue Fan; Xulin Liu; Mingxin Zhang; Zuolin Jin; Jie Gao (Progress in Orthodontics)
Abstract Objective Molar sequential distalization with clear aligners was advantageous. However, the effect of periodontal status on it has yet to be investigated. This study aimed to analyze the influence of the different periodontal states on molar distalization to reduce the adverse mechanical stimulation caused by periodontal states by the different stagings of movement and further explore therapeutic recommendations for clinical practice. Methods To ascertain the initial displacement of dentition and periodontal ligament (PDL) hydrostatic stress, finite element models (FEMs) were developed. These models included the distalization of the second molars (Step A) and the first molar (Step B) in three distinct periodontal conditions (simulating the periodontal state of mild, moderate, and severe periodontitis) and three distinct distances (0.10 mm, 0.18 mm, 0.25 mm). Results Periodontal status affected the tooth movement during molar distalization. During the molar distalization with 0.25 mm step distance, the initial displacement of the molar was greater in the model with worse periodontal condition. However, it did not increase the efficiency of tooth movement because the initial displacement is accompanied by tipping. Moreover, the second molar relapse to mesialization for a reaction from the first molar distalization affected efficiency. Fortunately, reducing the step distance could control those undesired tooth movements positively associated with alveolar bone resorption. Limitations The finite element method cannot simulate complex periodontal conditions in clinical practice. Conclusion To reduce the undesired tipping and relapse, the personalized staging of movement should be designed according to the periodontal condition. Designing 0.18 mm step distance for patients with 1/3 alveolar bone resorption is recommended, whereas patients with 1/2 alveolar bone resorption need 0.1 mm. These recommendations can guide orthodontists in designing effective treatment plans for patients with varying degrees of periodontal disease.